Novel NPRL3 variant associated with sleep-related hypermotor epilepsy: a case report and educational review - Broggi, Serena; Poppert, Kai-Nicolas; Mauritz, Matthias; Kalss, Gudrun; Leitinger, Markus; Abicht, Angela; Trinka, Eugen; Rossini, Fabio (Frontiers in Neuroscience, 2026)
IntroductionSleep-related hypermotor epilepsy (SHE) is a rare epileptic syndrome characterized by nocturnal seizures that predominantly arise during sleep, featuring complex motor behaviors. Pathogenic variants in the nitrogen permease regulator-like 3 (NPRL3) gene and other regulators of the mTOR pathway have been linked to diverse epilepsy phenotypes, including SHE. SHE is challenging to diagnose due to its diverse presentations, overlap with non-epileptic sleep disorders, and semiological similarities to functional/dissociative seizures (FDS).Case reportWe present the case of a 61-year-old woman with a lifelong history of nocturnal paroxysmal events and focal epilepsy. She experienced stereotyped nocturnal episodes of focal motor seizures with retained consciousness, characterized by hyperkinetic activity and asymmetric posturing. Despite multiple antiseizure medications (ASMs), only carbamazepine (CBZ) provided long-term seizure freedom. Genetic testing revealed a novel heterozygous mutation in the NPRL3 gene.DiscussionThis case highlights the diagnostic challenges of SHE and the importance of genetic testing in drug-resistant epilepsy. The identified NPRL3 mutation shows the genetic complexity of SHE and its implications for treatment.